Antibiotic contaminants reduced the treatment efficiency of UV-C on Microcystis aeruginosa through hormesis. (June 2020) - Jiang, Yunhan; Liu, Ying; Zhang, Jian
Abstract: Antibiotic contaminants exert stimulatory hormetic effects in cyanobacteria at low (ng L −1 ) concentrations, which may interfere with the control of cyanobacterial bloom in aquatic environments exhibiting combined pollution. This study investigated the influence of a mixture of four popular antibiotics (sulfamethoxazole, amoxicillin, ciprofloxacin, and tetracycline) during the application of UV-C irradiation for controlling the bloom of Microcystis aeruginosa. In the absence of antibiotics, 100–500 mJ cm −2 UV-C irradiation reduced cell density, growth rate, chlorophyll a content, Fv /Fm value and microcystin concentration in M. aeruginosa in a dose-dependent manner through the downregulation of proteins related to cell division, chlorophyll synthesis, photosynthesis and microcystin synthesis. UV-C irradiation stimulated microcystin release through the upregulation of the microcystin release regulatory protein (mcyH). The presence of 40 ng L −1 antibiotic mixture during UV-C treatment significantly reduced ( p < 0.05) the treatment efficiency of 100–300 mJ cm −2 UV-C on microcystin concentration, while 80 and 160 ng L −1 antibiotic mixture significantly reduced ( p < 0.05) the treatment efficiency of 100–500 mJ cm −2 UV-C on cell density and microcystin concentration. The antibiotic mixture alleviated the toxicity of UV-C on M. aeruginosa through a significant stimulation of photosynthetic activity ( p < 0.05) and the upregulation of proteins involved in photosynthesis, biosynthesis, protein expression, and DNA repair. Microcystin release in UV-C-treated cyanobacterial cells was further stimulated by the antibiotic mixture through the upregulation of mcyH and four ATP-binding cassette transport proteins. The interference effects of antibiotic contaminants should be fully considered when UV-C is applied to control cyanobacterial bloom in antibiotic-polluted environments. In order to eliminate the interference effects of antibiotics, the concentration of each target antibiotic is suggested to be controlled below 5 ng L −1 before the application of UV-C irradiation. Graphical abstract: Image 1 Highlights: Mixed antibiotics reduce the toxicity of UV-C in Microcystis aeruginosa. UV-C induces proteomic responses towards photosynthesis inhibition and ROS formation. Antibiotics stimulate DNA repair, growth and photosynthesis in UV-C treated cells. Antibiotics promote microcystin pollution by upregulating microcystin synthetases. Antibiotics should be controlled below safe threshold before UV-C treatment. Abstract : Main finding of the work: Coexisting antibiotic contaminants reduced the treatment efficiency of UV-C on Microcystis aeruginosa through the regulation of physiological activities and proteomic expression.